Lustra, symptomy i głębsze znaczenie. Lena Magnone, Konopnicka. Lustra i symptomy, Gdańsk 2011, wyd. słowo/obraz terytoria, 575 ss. - Mazan, Bogdan (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2012)
This was the title of a review of the book Konopnicka. Lustra i symptomy (słowo/obraz terytoria, Gdańsk 2011, p. 575) by Lena Magnore. The book is an abridged and edited version of her doctoral thesis. Opinions in my review are presented in a form of notes from reading academic literature. The purpose of Magnore’s book was a discussion with the homogeneous image of Konopnicka’s life and writings and attempt to make her image consistent. In order to achieve this goal, the author used modern methodologies and selected categories of the contemporary humanities, mostly psychoanalysis and gender studies. As a result, Konopnicka appears as a woman seen through the prism of charm and fear of femininity. The book allows to look at Konopnicka’s writing in different and unorthodox manner, provides sensitive documentation of difficult and painful issues. The use of “psychoanalytical key of interpretation” makes it possible to see different mechanism of denying femininity, important “wounds of text”, motifs unknown in traditional writings about maternity, different forms of hysteria.